ANALISIS TINGKAT KEPUASAN PENGGUNA SISTEM INFORMASI UJIAN AKHIR SEMESTER MENGGUNAKAN METODE END USER COMPUTING SATISFACTION (EUCS) - Nanny Raras Setyoningrum; Prihandoko Prihandoko (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2018)
The use of information technology in the world of education has developed a lot, especially in universities. As an example of the application of college-level information technology is the delivery of information presented through the official website of the Higher Education. One of the web-based systems owned by the Sekolah Tinggi Teknologi Indonesia Tanjungpinang is the Final Semester Examination Information System (SIUAS). With this technology, the final semester exam no longer uses the manual method with answer sheets but students can answer directly on a computer or laptop. Satisfaction level analysis is important to know the extent of expectations and realities of system users in an effort to achieve the perfection of an information system and can meet user expectations. One method in analyzing user satisfaction is end user computing satisfaction (EUCS). Dimensions contained in EUCS consist of content, accuracy, format, ease of use and timeliness. This type of research is descriptive research that is intended to describe the phenomena that exist, which take place now or in the past. Data collection methods include observation, interviews and questionnaires with a sample of 47 respondents who are active users of SIUAS. The results of the analysis of the level of satisfaction of SIUAS users of the Tanjungpinang Indonesian Institute of Technology used the EUCS method of 87.01% with a gap of 12.99% meaning that the user is in a very satisfied category range. Of the five dimensions, the variable easy of use has the smallest gap, namely 9.9% while the biggest gap is in the variable timeliness, which is 17.52%.